Impact of Locally Isolated Probiotics on Growth Performances, Haemato-Biochemical Profiles and Cecal Microflora of Broiler - Biswas, Lita; Beg, Md. Anwarul Haque; Saiful Islam, K.B.M. (International Journal of Poultry Science, 2020)
Background and Objective: Increasing bacterial resistance to antibiotics has contributed to the urge for the development of alternatives to antibiotics. Accordingly, probiotics have received great attention as an alternative to synthetic antibiotics. Locally isolated probiotics may have beneficial effects on animal health and stand for a better alternative to antibiotics. Therefore, the effects of supplementation of locally isolated Lactobacillus salivarius and Bifidobacterium thermophilum on growth performances, haemato-biochemical profiles and cecal microbial compositions of broilers were studied in this experiment. Materials and Methods: A total of 320 day-old unsexed broiler chicks were allocated to 4 treatment groups each containing 4 replicates of 20 chicks. Groups included basal diet (control); control plus Doxycyclin (AGP); control plus L. salivarius (probiotic-I) and control plus B. thermophilum (probiotic-II). Experimental birds were raised for 28 days. Growth performances, haemato-biochemical profiles and cecal microbial composition were analyzed following standard protocol. Results: Probiotic-I impacted significantly on increased body weight and decreased FCR without significant effect in feed consumption, dressing and survivability rate. Probiotics supplementation resulted in higher liver weight in probiotic-I. Significantly higher Hb, RBC and WBC counts were observed in probiotics supplemented groups compared with AGP and control groups. However, total cholesterol, DLCs, PCV, MCV, MCHC were not affected by probiotics supplementation. Total Coliform and Salmonella counts were significantly reduced and Lactobacilli were significantly increased with probiotics supplementation. Conclusion: Locally isolated L. salivarius could be considered as a good potential probiotic for broiler which could be a feasible alternative to antibiotics in broiler diet at finisher stage.